The Role and Function of Islamic Boarding School: An Indonesian Context - Thahir, Mustain (TAWARIKH, 2014)
ABSTRACT: Islamic boarding school or âpesantrenâ, as one of the educational institutions, has recognized a big influence in developing the educational world, especially in Indonesian society. Islamic boarding school is also believed to be an alternative for solving various problems of education that occurs at this time. Islamic boarding school is the oldest institution of Islamic education in Indonesia. According to experts, the Islamic boarding school is able called a âreligious schoolâ when meet five requirements, namely: (1) âkyaiâ or Muslim religious teacher or leader in Java; (2) âpondokâ or lodge; (3) âmesjidâ or mosque; (4) âsantriâ or Islamic students; and (5) âkitab kuningâ or yellow book reading or Islamic classic book. This article tries to elaborate the role and function of Islamic boarding school in Indonesia, with related to the religious school of âDarud Dakwah wal-Irsyadâ (DDI) Mangkoso Barru in South Sulawesi, Indonesia. The Islamic boarding school, as a community and an institution that is large in number and widely spread in various parts of the Indonesian country, has had much to share in the formation of the Indonesian people fully religious. Therefore, the institution has delivered many leaders in the past, present, and also in the future. The graduates of Islamic boarding school, no doubt, many of them have taken an active participation in nation building. But, on the other hand, there is also the notion that graduates of Islamic boarding school are hard invited forward. This is because the education system in the Islamic boarding school is mostly still traditional.KEY WORDS: Islamic boarding school, role and function, religious school, nation building, traditional education, and Indonesian society.About the Author: Dr. Mustain Thahir is a Senior Lecturer at the Faculty of Education and Teacher Training UVRI (Veteran University of the Republic of Indonesia), Jalan Baruga Raya, Antang, Makassar, South Sulawesi, Indonesia. Corresponding author is aspensi@yahoo.comHow to cite this article? Thahir, Mustain. (2014). âThe Role and Function of Islamic Boarding School: An Indonesian Contextâ in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.197-208. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 19, 2014); Revised (March 22, 2014); and Published (April 28, 2014).